Adaptation-induced Tourism for Consumers of Literature on Screen: the Experience of Jane Austen Fans - Pennacchia, Maddalena (Almatourism - Journal of Tourism, Culture and Territorial Development, 2015)
My aim in this article is that of starting to relate the expanding research field of adaptation studies to the subject area of film-induced tourism. Adaptations are a specific typology of films: that is, films whose story was not originally intended for the screen but, more often than not, for the written page, and has, therefore, been ‘translated’ into a new medium. The phenomenon of adaptation has been at the center of a heated debate for a few years now, but the specific link between adaptation and tourism has not yet been studied in its own right. In my article I question why and how adaptations of literary texts for the screen can induce a desire to visit film locations (actual geographical places) in readers who are also inclined to enjoy the experience of “literature on screen”. In order to do this, I focus on the case study of adaptations from Jane Austen’s novels and on a specific kind of tourists, the so called ‘Janeites’, or Austen fans.